2003
DOI: 10.1086/378356
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Live, Attenuated Vaccine against Japanese Encephalitis (ChimeriVax‐JE): Phase 2 Clinical Trials for Safety and Immunogenicity, Effect of Vaccine Dose and Schedule, and Memory Response to Challenge with Inactivated Japanese Encephalitis Antigen

Abstract: ChimeriVax-JE is a live, attenuated vaccine against Japanese encephalitis, using yellow fever (YF) 17D vaccine as a vector. In a double-blind phase 2 trial, 99 adults received vaccine, placebo, or YF 17D vaccine (YF-VAX). ChimeriVax-JE was well tolerated, with no differences in adverse events between treatment groups. Viremias resulting from administration of ChimeriVax-JE and YF-VAX were of short duration and low titer; 82 (94%) of 87 subjects administered graded doses (1.8-5.8 log(10)) of ChimeriVax-JE devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
136
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(150 citation statements)
references
References 39 publications
11
136
1
Order By: Relevance
“…Data from Phase 1 and 2 trials of this vaccine indicated that it was well tolerated and highly immunogenic at all dose levels tested (5.8 to 1.8 log 10 PFU). 17 We found no unexpected safety concerns with ChimeriVax™-DEN2 vaccinations. The profile of AEs observed following ChimeriVax™-DEN2-vaccination was similar to that observed after vaccination with YF-VAX ® .…”
Section: Discussionmentioning
confidence: 61%
“…Data from Phase 1 and 2 trials of this vaccine indicated that it was well tolerated and highly immunogenic at all dose levels tested (5.8 to 1.8 log 10 PFU). 17 We found no unexpected safety concerns with ChimeriVax™-DEN2 vaccinations. The profile of AEs observed following ChimeriVax™-DEN2-vaccination was similar to that observed after vaccination with YF-VAX ® .…”
Section: Discussionmentioning
confidence: 61%
“…Subjects who received the lower (3 log 10 PFU) dose of ChimeriVax-WN02 had statistically higher viremias than those receiving a dose 100 times higher. This paradoxical response has been observed in the case of YF 17D vaccine (5) and a chimeric vaccine against Japanese encephalitis (19) and may be due to a lower innate and delayed adaptive immune response to the lower dose. Control of the early phase of flavivirus infection depends on type 1 IFN synthesis by plasmacytoid DC (20).…”
Section: Discussionmentioning
confidence: 93%
“…Future studies will address safety and tolerability for elderly and infirm persons at greatest risk of severe WN virus disease (18). Nearly all subjects experienced a transient low viremia, an expected observation with YF 17D (5) and other chimeric vaccines (19). Subjects who received the lower (3 log 10 PFU) dose of ChimeriVax-WN02 had statistically higher viremias than those receiving a dose 100 times higher.…”
Section: Discussionmentioning
confidence: 93%
“…Recent clinical studies have indicated that antigenic chimeric flaviviruses are attenuated and immunogenic in human volunteers and may serve as live attenuated virus vaccines for protection against disease caused by DEN, JE, WN, and TBE viruses [27][28][29][30][31]. These positive results observed in several clinical trials support the further development and study of antigenic chimeric flaviviruses.…”
Section: Discussionmentioning
confidence: 87%